SAT0035 Chondroprotective Effects of IL-6 Inhibition Through Blockade of the STAT3 Pathway. (9th June 2015) - Latourte, A.; Cherifi, C.; Ea, H.-K.; Bouaziz, W.; Funck-Brentano, T.; Cohen Solal, M.; Hay, E.; Richette, P.
Abstract : Background: High levels of interleukin-6 (IL-6) have been found in the synovial fluid of patients with osteoarthritis (OA), suggesting that IL-6 may be involved in the pathogenesis of OA. Objectives: To investigate the effects of IL-6 in chondrocytes and to determine its main signalling pathways. To study the impact of IL-6 inhibition in an experimental mice model of OA. Methods: The effects of IL-6 (10-50-100 ng/mL) were determined in vitro (primary culture of mouse chondrocytes) and ex vivo (mouse femoral head articular cartilage). Proteoglycan content (Alcian blue and Safranin O staining, DMM blue assay), expression of catabolic factors (qPCR, Western Blot, immunostaining), NO and PGE2 production and apoptosis (TUNEL assay) were evaluated. IL-6-induced signalling pathways were determined by Western Blot. The impact of STAT3 blockade was investigated using a specific inhibitor – Stattic – ex vivo and in a mice model of OA induced by destabilization of the medial meniscus (DMM). Results: In vitro and ex vivo, IL-6 dose-dependently induced a dramatic loss of proteoglycan content through an increase in the expression of MMP3, MMP13, ADAMTS4 and ADAMTS5. By contrast, IL-6 had no effect on col2, aggrecan, col10 or VEGF. IL-6 induced chondrocytes apoptosis without increasing NO or PGE2 production. Inhibition of STAT3 by Stattic counteracted the catabolic and pro-apoptotic effects of IL-6 ex vivo. Finally, we orally administrated either Stattic (25 mg/kg/2d) or a saline for 6 weeks in C57/Bl6 mice (n=18) subjected to DMM. The severity of the OA lesions as assessed with the OARSI histological score was significantly lower in the Stattic group: 2.65±1.44 vs. 4.5±0.93 (p=0, 004). Conclusions: Our findings indicate that IL-6 has numerous catabolic effects in cartilage, mainly mediated by STAT3. STAT3 blockade protects against DMM-induced OA in mice, suggesting that IL-6 might be a promising therapeutic target in OA. Disclosure of Interest: None declared